Opportunistic Grazing to Restore Soil Health, Ecosystem Function and Ecosystem Services – MELIA study - Louhaichi, Mounir; Ouled Belgacem, Azaiez; Hassan, Sawsan; Nefzaoui, Ali (International Center for Agricultural Research in the Dry Areas, 2025)
A MELIA study on Opportunistic Grazing to Restore Soil Health, Ecosystem Function, and Ecosystem Services in Tunisia examined the effectiveness of this approach in rehabilitating degraded arid rangelands. The study evaluated improvements in productivity, biodiversity, and soil health while analyzing the socioeconomic benefits for livestock productivity and ecosystem services. Additionally, it explored the role of gender and community-led decision-making in adopting sustainable grazing practices. The findings provided valuable insights for policymakers seeking to balance livestock production with long-term rangeland sustainability.